DAMPAK AKTIVITAS OLAHRAGA TERHADAP STRES AKADEMIK PADA PESERTA DIDIK - Widohardhono, Rachman; Rachman, Nabila; Jannah, Miftakhul (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: In the academic process, students have the potential to experience academic stress, among others, due to high expectations, a lot of incoming information, academic pressure, and unrealistic ambitions. One of the activities carried out is sports activities. Objective: The objective of the study was to assess the relationship between sport activity and academic stress. Method: A total of 65 student were involved in this study. Age range of 14–17 years, Data obtained from Global Physical Activity Questionnaire (GPAQ) and reported the number of days and duration of activities they spent on studying or working, travelling, and recreational activities. All responses as to the duration were converted from hours into METs. Data academic stress obtained from Perception of Academic Stress Scale. Statistical analysis using analysis of varian was performed using JASP for window version 0.14.1 Result: The research results show an F value of 3.304 with a p value of 0.043 (<0.05). Conclusion: There is a significant difference between the level of sports activity and academic stress. The higher the level of sports activity, the lower the academic stress. Keywords: Academic stress, sport activity, student. Latar Belakang: Peserta didik dalam dalam proses akademik ada potensi mengalami stres akademik antara lain karena ekspektasi yang tinggi, banyaknya informasi yang masuk, tekanan akademis, ambisi yang tidak realistis. Salah satu kegiatan yang dilakukan adalah aktivitas olahraga. Tujuan: Penelitian ini bertujuan untuk menilai hubungan antara aktivitas olahraga dan stres akademik siswa Sekolah Menengah Atas. Metode: Sebanyak 65 siswa dilibatkan dalam penelitian ini. Rentang usia 14–17 tahun. Data diperoleh dari Global Physical Activity Questionnaire (GPAQ) dan melaporkan jumlah hari dan durasi aktivitas yang mereka habiskan untuk belajar atau bekerja, bepergian, dan aktivitas rekreasi. Semua tanggapan mengenai durasi diubah dari jam menjadi MET. Data stres akademik diperoleh dari Skala Persepsi Stres Akademik. Analisis statistik menggunakan analisis varian dilakukan dengan menggunakan JASP for window versi 0.14.1. Hasil: Hasil penelitian menunjukkan nilai F sebesar 3,304 dengan nilai p 0,043 (<0,05). Kesimpulan: Terdapat perbedaan yang signifikan antara tingkat aktivitas olahraga dengan stres akademik. Semakin tinggi tingkat aktivitas olahraga maka semakin rendah stres akademik. Kata kunci: Stress akademik, aktivitas olahraga, peserta didik.